CRUSADES: RELIGIOUS AND POLITICAL OBJECTIVES, AND THEIR IMPACT ON WORLD HISTORY (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
The article explores the Crusades, examining their religious and political objectives, and how these campaigns impacted world history. It discusses the motivations behind the Crusades, including the desire to reclaim sacred lands and the political ambitions of European powers. The influence of these wars on trade, culture, and the relationships between different civilizations is also analyzed, highlighting their long-lasting effects on Europe and the Middle East.